Interactive Effects of Stream Sizes and Furrow Geometry on Furrow Irrigation Erosion, Growth and Yield of Maize in Samaru-Zaria Northern Nigeria - J. M. Dibal; A. U. Bashir; N. A. Abubakar; B. Baraya (Arid Zone Journal of Engineering, Technology and Environment, 2017)
Erroneous choices of furrow irrigation characteristics trigger soil erosion with several negative impacts. Soil erosion and sediment yield in furrow irrigation has not been fully evaluated in Samaru-Zaria. This study sought to establish the interactive effects of irrigation stream sizes (2.5, 1.5, and 0.5 l/s); furrow lengths (90 and 45 m); and furrow widths (0.75 and 0.9 m) randomized in a split-plot design on soil erosion, growth, and yield of maize (Zea mays L.). The 90- and 4-m long furrows were herein referred to as long and short furrows respectively, while the 0.75- and 0.9-wide furrows were termed narrow and wide furrows for convenience sake. The field experiment involved irrigating maize on the normal straight furrow irrigation method on a sandy loam soil in the Irrigation Research Farm of Institute for Agricultural Research (I.A.R), Samaru-Zaria, in 2009/2010 and 2010/2011 dry irrigation seasons. Maize plants irrigated at 2.5 l/s on long narrow furrows were most stunted (118.396 m) while irrigating at 1.5 l/s in long wide furrows produced tallest maize plants (169.034 m). Irrigating at 2.5 l/s in long narrow furrows delayed days to 50 % tasseling (77.632 days) and days to 50 % plant maturity (79.125 days). Highest average sediment concentration (41.697 g/l) and runoff volume (147.861 ltr) were recorded in short narrow furrows irrigated at 2.5 l/s. The long narrow furrows irrigated at 2.5 l/s produced largest soil erosion (0.603 t/ha). Best grain yield (5.19 t/ha) was achieved in long wide furrows irrigated at 1.5 l/s. The severity of soil erosion and its impact on crop production were greater in long narrow furrow irrigated at 2.5 l/s. Irrigation at 1.5 l/s in long wide furrows trimmed down soil erosion and better maize growth and yields. Furrow irrigation should be designed and operated professionally to avert ecological deterioration, and sustain soil’s quality and crop productivity.